2008
DOI: 10.1038/ki.2008.206
|View full text |Cite
|
Sign up to set email alerts
|

Urinary exosomal transcription factors, a new class of biomarkers for renal disease

Abstract: Urinary exosomes are excreted from all nephron segments and constitute a rich source of intracellular kidney injury biomarkers. To study whether they contain transcription factors, we collected urine from two acute kidney injury models (cisplatin or ischemia-reperfusion), two podocyte injury models (puromycin-treated rats or podocin-Vpr transgenic mice) and from patients with focal segmental glomerulosclerosis, acute kidney injury and matched controls. Exosomes were isolated by differential centrifugation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
196
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(208 citation statements)
references
References 59 publications
7
196
1
4
Order By: Relevance
“…10 Exosomes can, therefore, incorporate cargo, such as soluble proteins, mRNAs, microRNAs (miRNAs), noncoding RNA, mitochondrial DNA, transcription factors, and other cytosolic components and molecules. 10,22,23 After these vesicles fuse with the plasma membranes of the parent cell, they are released as exosomes into the extracellular environment ( Figure 1). Interestingly, the lipid-bilayered exosomes seem to be protected from RNAses, 24,25 sheltering the genetic cargo in exosomes.…”
Section: Characterization Of Evsmentioning
confidence: 99%
“…10 Exosomes can, therefore, incorporate cargo, such as soluble proteins, mRNAs, microRNAs (miRNAs), noncoding RNA, mitochondrial DNA, transcription factors, and other cytosolic components and molecules. 10,22,23 After these vesicles fuse with the plasma membranes of the parent cell, they are released as exosomes into the extracellular environment ( Figure 1). Interestingly, the lipid-bilayered exosomes seem to be protected from RNAses, 24,25 sheltering the genetic cargo in exosomes.…”
Section: Characterization Of Evsmentioning
confidence: 99%
“…There was a reduction of mitochondrial cytochrome C oxidase in the diabetic kidneys compared with control kidneys (Figure 4, A and B). Second, mitochondrial DNA in urine exosomes was measured because urine exosomes are largely derived from renal epithelial cells 17 Figure 4C). The reduction in mitochondrial protein and mtDNA indicate an overall reduction in mitochondrial biogenesis.…”
Section: Validation Of Biochemical Pathwaysmentioning
confidence: 99%
“…18 Therefore, we explored the possibility of miR-494, an ATF3-related miRNA, becoming an alternative indicator for AKI. We found that, in mice, urinary miR-494 levels were increased 1 hour after reperfusion, but the elevated levels were reduced dramatically 12 hours later ( Figure 7A).…”
Section: Mir-494 Enhanced Il-6 Induction Associated With a Reduction mentioning
confidence: 99%